Effects of down-regulated steroidogenic factor-1 on ACTH and potassium chloride-induced steroid synthesis in H295R cells - Hu, D; Wang, X; Cao, R; Ding, X (Cellular and Molecular Biology, 2015)
The prevalence of adrenal diseases in the cortex is more common than that in the medulla in the form of hormone disorder or neoplasm. Steroidogenic factor-1 (SF-1) is important in regulating aldosterone synthase (CYP11B2) and cortisol synthase (CYP11B1). SF-1 is increased in aldosterone-producing adenoma (APA) and cortisol-producing adenoma (CPA). Overexpression of SF-1 has been extensively studied, but the available in-depth information regarding the effects of downregulated SF-1 on CYP11B2/CYP11B1 and their regulators is limited. In this paper, we attempted to investigate the effects of downregulated SF-1 on aldosterone to adrenocorticotropic hormone (ACTH) and potassium chloride (KCl) stimulation and those on cortisol to ACTH stimulation through RNA interference in acute and chronic phases. Downregulated SF-1 decreased the sensitivity of aldosterone to ACTH/KCl and that of cortisol to ACTH stimulation. This study provides new insights into the influence of SF-1 on adrenocortical diseases by considering the effects of SF-1 on regulation.